The 3D printing of patient-specific kidney models to facilitate pre-surgical planning of renal cell carcinoma using CT datasets - Lupulescu, Catalina; Sun, Zhonghua (The Australasian Medical Journal pty ltd., 2021)
Background: Three-dimensional (3D) printing in medicine is a rapidly growing field of research. This study endeavoured to investigate the feasibility of using 3D-printed kidney models for pre-surgical planning of renal cell carcinoma (RCC) resection and provide insight into medical 3D printing technologies and materials.